Development of IPAS worksheet using problem-based learning to improve critical thinking - Maisarah Nasution; Ashar Hasairin; Hasruddin Hasruddin (Inovasi Kurikulum, 2025)
This research aimed to develop an instructional worksheet (LKPD) for Science and Social Studies (IPAS) based on the Problem-Based Learning (PBL) model assisted by Canva, which is valid, practical, and effective in improving elementary students’ critical thinking skills. The development was motivated by students’ low critical thinking abilities in IPAS and the lack of interactive teaching materials aligned with the Merdeka Curriculum. This study employed Research and Development (RnD) with a modified ADDIE model consisting of three stages: analysis, design, and development. The subjects included material experts, media experts, language experts, fourth-grade teachers, and fourth-grade students of SD IT Ummu Hafidzah, Deli Serdang. The instruments consisted of validation sheets, practicality questionnaires, and critical thinking tests. The results indicated that the LKPD was highly valid with average scores above 80% across all validation aspects. Its practicality was confirmed by positive feedback from teachers and students. Effectiveness testing through independent sample t-test and N-Gain analysis showed a significant increase in students’ critical thinking skills in the experimental class. These findings demonstrate that the PBL-based LKPD assisted by Canva is sufficiently effective in enhancing critical thinking skills.   Abstrak Penelitian ini bertujuan untuk mengembangkan Lembar Kerja Peserta Didik (LKPD) mata pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) berbasis model Problem Based Learning (PBL) berbantuan Canva yang valid, praktis, dan efektif dalam meningkatkan kemampuan berpikir kritis peserta didik sekolah dasar. Pengembangan dilakukan karena lemahnya daya kritis peserta didik dalam pembelajaran IPAS serta terbatasnya media ajar interaktif yang sesuai dengan karakteristik Kurikulum Merdeka. Jenis penelitian ini adalah Research and Development (RnD) dengan model ADDIE yang dimodifikasi menjadi tiga tahap, yaitu analisis, desain, dan pengembangan. Subjek penelitian terdiri dari ahli materi, ahli media, ahli bahasa, guru kelas IV, serta peserta didik kelas IV SD IT Ummu Hafidzah Deli Serdang. Instrumen yang digunakan berupa angket validasi, angket praktikalitas, serta tes kemampuan berpikir kritis. Hasil penelitian menunjukkan bahwa LKPD tergolong sangat layak dengan skor rata-rata di atas 80% pada seluruh aspek validasi. Kepraktisan LKPD juga tinggi berdasarkan tanggapan guru dan peserta didik. Uji efektivitas menggunakan uji independent sample t-test dan N-Gain menunjukkan peningkatan signifikan kemampuan berpikir kritis pada kelas eksperimen. Hasil tersebut menunjukkan bahwa LKPD berbasis PBL berbantuan Canva cukup efektif dalam meningkatkan kemampuan berpikir kritis. Kata Kunci: berpikir kritis; LKPD; problem-based learning